CEMARAN BAKTERI PATOGENIK PADA SUSU SAPI SEGAR DAN RESISTENSINYA TERHADAP ANTIBIOTIKA - Anni Kusumaningsih; Tati Ariyanti (Research Center for Biology-Indonesian Institute of Sciences, 2013)
Fresh milk is a beverage with high protein contents that can be consumed either directly or as ingredient supplement into safely and healthy food. However, the milk also as a good media for development of pathogenic bacteria that also dangerous for human health. The aim of this research was to determine pathogenic bacteria contamination in fresh milk and its antibiotic resistance profiles to several antibiotics. Fresh milk samples were taken from milk cans belong to the farmers at 34 dairy cows centre in Cibungbulang, Bogor, West Java. The quantitative determination was conducted on 34 milk samples. Several parameters examined were based on the Indonesian Nasional Standard (Standar Nasional Indonesia/SNI) No. 01-3141-1998 for Fresh Dairy Milk and SNI No. 7833-2009, such as total bacteria and coliform. The qualitative examination result for isolation and identification of bacteria were found that the milk samples consisted of 41.18% E. coli, 23.53% Streptococcus Gorup B, 8.82% Staphylococcus aureus, and none for Salmonella. The antibiotic resistence profiles were tested to 5 antibiotics. It showed that Escherichia coli isolates were resitance to penicilline (14.3%), oxytetracycline (21.4%), chloramphenicole (57.1%), and streptomycin (28.6%), whereas those Streptococcus Group B isolates were resistance to penicilline (12.5%), Oxytetracycline (37.5%), chloramphenicole (25.0%), streptomucin (87.5%), and ciprofloxacin (87.5%). Multiresistance of E. coli were found against 2 antibiotics, whereas Streptococcus against 2-3 antibiotics. This research indicated that fresh milk samples taken from farmers at Cibungbungang, Bogor were contaminated with several pathogenic bacteria and mostly highly resistance to 5 antibiotics testing.